The Moderating Effect of Demographics in the Relationship between Graduate Employability and Course Outcomes Contribution - Bagares, Lovelyn M. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This study aimed to determine the moderating effect of demographics in the relationship between graduate employability and course outcomes contribution. In this study, graduate employability is evaluated by allowing graduates to self-assess their skills. Additionally, graduates assess how their course outcomes have contributed to their graduate skills. This study utilized the descriptive correlational design with moderation analysis to determine the significant relationship among the variables. Stratified Random sampling was used with a total sample size of 125 employed graduates. The statistical tools employed in the study were frequency and percentage distribution, mean and standard deviation, Analysis of variance, Regression analysis, and Moderation analysis. The findings revealed no significant difference in the graduate's employability when respondents were grouped according to profile. A test of influence was conducted between graduate employability and course outcomes contribution, with a coefficient of 1.032 and p-value<0.001 indicating a strong significant relationship. However, it was found that demographics have no moderating effect on the relationship between graduate employability and course outcomes contributions. In conclusion, graduate employability is significantly influence by course outcomes contribution, which established the fact that the stronger the curriculum is the higher the graduate employability of the graduates. Curriculum intervention is simplified eliminating profile segregation, it makes it easier to give activity, seminar, trainings and other activities to graduates. Overall, regardless of future career path the graduates would take, the curriculum should have a well-grounded curriculum and activity to nourished versatile skills for graduates.